Analysis of Students' Mathematical Connections Ability on HOTS Questions Based on Jambi Culture in View of Personality Types - Putri, Rahmi; Vrasetya, Arshinta; Nasution, Eline Yanty Putri; Casanova, Anriany (Jurnal Pendidikan MIPA, 2025)
This study aims to analyze students’ mathematical connections ability in solving Higher Order Thinking Skills (HOTS) problems based on Jambi culture, viewed from judging and perceiving personality types as categorized by the Myers-Briggs Type Indicator (MBTI). A total of 21 twelfth-grade students from SMA Negeri 3 Sungai Penuh participated in the MBTI test for personality identification. Based on the highest scores in each category, four students (two with judging and two with perceiving personalities) were purposefully selected for detailed analysis. A qualitative case study approach was employed, utilizing HOTS problems with local cultural stimuli, specifically the Kajang Leko traditional house and Padamaran cake, along with structured interview guidelines. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results revealed that students with judging personality types had higher scores (average 75%, high category) in mathematical connections ability compared to those with perceiving types (62.5%, moderate category). This difference can be attributed to the characteristics of judging individuals, who tend to be more systematic, structured, and consistent in constructing problem-solving steps, allowing them to connect mathematical concepts more logically. In contrast, perceiving students as flexible and spontaneous tended to be less organized, resulting in difficulties establishing comprehensive conceptual relationships. The novelty of this study lies in its integration of local Jambi culture as contextual stimuli in assessing mathematical connection ability based on personality types. The findings potentially diverge from previous studies, which suggested that perceiving types were more adept at making conceptual connections. This research indicates that local cultural contexts may influence students’ cognitive performance according to personality, highlighting the importance of incorporating cultural factors and individual characteristics into the design of mathematics instruction. Keywords: judging personality, perceiving personality, mathematical connections ability, HOTS questions, jambi culture.